Hungarian Monitoring, 18 March 1988 . [Magyar rádiófigyelő], 1988. március 18 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
Transcripts of Hungarian national radio programs produced by the Hungarian Monitoring Unit of Radio Free Europe/Radio Liberty. A magyar országos rádióadók műsorainak a Szabad Európa Rádió/Szabadság Rádió Magyar Monitoring Osztálya által készített átiratai. International Politics: - Summary of Gorbachev's visit to Yugoslavia - Soviet chief prosecutor on the demonstrations and their regulation - Talks in Moscow on the situation in Armenia and Azerbaijan - Poland: drop in real incomes Domestic Affairs: - József Marjai travels to the FRG for GATT meeting - Interview with Rezső Nyers - Forthcoming assessment of situation of those living in poverty - Hungarian friendship societies abroad meeting in Budapest - The Spring Festival has begun Economy: - Suzuki production in Hungary - Secretary of state for trade makes statement on prospects for stabilization Külpolitika: - Összefoglaló Gorbacsov jugoszláviai látogatásáról - A szovjet főügyész a tüntetésekről és azok szabályozásáról - Megbeszélések Moszkvában az örmény és azerbajdzsáni helyzetről - Lengyelország: csökkenő reáljövedelmek Belpolitika: - Marjai József a GATT ülésére utazott az NSZK-ban - Interjú Nyers Rezsővel - A szociálisan szegénységben élők helyzetéről készül felmérés - Külföldön működő magyar baráti társaságok budapesti tanácskozása - Megkezdődött a Tavaszi Fesztivál Gazdaság: - A Suzuki magyarországi gyártása - A kereskedelmi államtitkár nyilatkozata a stabilizációs kilátásokról